ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KAKAO DI INDONESIA - Vanni Yuliani Zulfikar; Ali Anis; Alpon Satrianto (Universitas Negeri Padang, 2018)
The purpose of this research are to determine and analyze the effect of land area, and labor on cocoa production accross province in Indonesia by using the Pooled Analysis equation. The results showed that the land area had a positive and significant effect on the production of cocoa in Indonesia, and labor had a positive and insignificant effect on the production of cocoa in Indonesia. From the results of the study, it is suggested that the government be able to carry out a program to develop the cocoa plantation sector, and provide training to farmers so that the amount of cocoa production in Indonesia can increase and farmers' income also increases.